La evolución de la relación salarial durante la post convertibilidad - Julio César Neffa (Revue de la Régulation)
This contribution synthesizes a decade of research. It analyses the dynamics of the wage-labor nexus after the convertibility period, i.e. from 2002 until the end of 2011. It also scrutinizes the most salient constraints arising in the development mode after the subprime crisis that limit its viability. These problems are becoming more obvious since the beginning of President Cristina Fernández de Kirchner second term.